Integrative regulation of middle cortex formation: from classic modules to emerging pathways - Kim, Seung Woo; Chang, Kwang Suk; Kang, Minhee; Lim, Jun (Frontiers in Plant Science, 2025)
Generation of distinct cell types through asymmetric cell division (ACD) is a fundamental developmental process in multicellular organisms. Therefore, controlling when and where ACDs occur is essential for the production of new cells and tissues. The Arabidopsis (Arabidopsis thaliana) root has emerged as a powerful model for studying this process because its cell division patterns are highly stereotyped and easily observed. Within the ground tissue, periclinal ACDs in the endodermis generate the middle cortex (MC) post-embryonically, which serves as a hallmark of root maturation. Since the first description of MC formation, extensive research has identified the genetic and environmental cues that either promote or suppress its initiation. Over the past two decades, studies have revealed that MC formation is orchestrated by a regulatory hub centered on the SHORT-ROOT (SHR)–SCARECROW (SCR) transcriptional module and its target, CYCLIND6;1 (CYCD6;1). This core pathway is fine-tuned by multiple regulators, including transcriptional co-activators, repressors, and integrators of gibberellic acid (GA) signaling. Recent advances have uncovered new roles for transcription factors, chromatin regulators, redox enzymes, and receptor-like kinases in linking hormonal signals and positional cues to the SHR–SCR–CYCD6;1 regulatory hub. Together, these pathways ensure that MC formation occurs at the right time, place, and extent. This review summarizes advances in MC regulation, highlighting how transcriptional, hormonal, and positional networks integrate to ensure developmental plasticity in plant roots.